Relação entre avaliação nutricional e escore prognóstico de Glasgow em pacientes com câncer de esôfago e estômago - Jacqueline Braga da Silva (2011)
Relationship between weight loss and the presence of inflammation has been described in patients with cancer. Both nutritional status and severity of inflammation may be associated with the development of complications during cancer treatment and survival time. Thus, the assessment of inflammation could be used as a tool to screen patients who may benefit from early nutritional interventions. In the present study it was evaluated the relationship between nutritional status, defined by the subjective global assessment (SGA), and the severity of inflammation as defined by the Glasgow prognostic score (GPS). In addition, we compared the diagnosis given by the SGA with other parameters of nutritional assessment, such as body mass index (BMI), triceps skinfold (TSF), midarm circumference (MAC), midarm muscle circumference (MAMC), phase angle (PA), adductor pollicis muscle thickness (APMT) and hand grip strength (HGS). This study enrolled 43 patients with cancer of the esophagus and stomach with a mean age of 64.7 ± 12.0 years. The nutritional status, according to the three categories of SGA was associated with the three categories of the Glasgow prognostic score (p < 0.05), and both the SGA and the GPS were associated with the presence of complications, but the GPS (ASC: 0.77, p < 0.05, CI = 0.580, 0.956) seems to be more accurate in identifying complications than the SGA (AUC: 0.679, p < 0.05, CI = 0.426, 0.931). Only the GPS was associated with survival time, as the mean survival was 86.7 days among patients with score of 0 and 72 days among patients with scores 1 and 2 (Log Rank < 0.05). When comparing the methods of nutritional assessment with the SGA it was found that MAC, MAMC, APMT, PA and HGS seem to be good parameters to differentiate nourished and malnourished patients